STUDY ON DEVELOPING APPROPRIATE UNLEADED GASOLINE SPECIFICATION FOR INDONESIA (2000-2010) - Rasdinal Ibrahim; Adiwar Adiwar; Mardono Mardono (Testing Center for Oil and Gas LEMIGAS, 2002)
Automotive fuels are significant sources of air pollution in most metropolitan areas. Motor gasoline is responsible for emission of carbon monoxide (CO), volatile organic compounds (VOC), nitrogen oxides (NOx), sulfur oxides (SOx) which all have adverse impacts on the environment and public health. In line with the implementation of Blue Sky Program, revision of the current gasoline specification needs be taken to improve the quality of Indonesia's gasoline to meet vehicle engine technology and environmental requirement with the global fuel specification harmonization as formulated in the World Wide Fuel Charter as reference. This study on developing of appropriate unleaded gasoline specification in Indonesia consists of examination of the key properties that influence the emissions, status and trend of current gasoline specification, comparison of Indonesia's gasoline specification with other countries and recommendation of the new unleaded gasoline specification options that match the implementation of Blue Sky Program in Indonesia and the scenario for its implementation.